How to read "Sandro from Chegem" by FazilIskander? (Language, ethnography, axiology) - Marina V. Bitokova (Кавказология, 2022)
In this article, the text of FazilIskander’s novel “Sandro from Chegem” is considered from the point of view of its correlation with the realities of Abkhazia in the 1900s-1960s, the structure of Abkhazian life and cultural phenomena that had a significant impact on the artistic originality of this work and the creative method of the author. It seems important to pay attention not to those factors that are often perceived by the reader (following critics and literary critics) as a decoration or an exotic decor for the semantic content the author implies when working on a novel. It is necessary to look at Iskander’sChegem epic from a new - Abkhaz-centric angle: that is, when reading the text, taking as a starting point the history and ethnography of the Abkhazian people (mainly the twentieth century), folklore tradition, the mentality of the people and many other factors.The presented article concerns only some of the showed aspects, in particular: attribution of the hero by one of his main social roles (toastmaster); definition of the boundaries of the chronotype of the novel - time and action (what is more in the first case, not only abstract Abkhazia is of great importance but also a very specific Abkhazian estate - its structure and functioning); features of the language of the novel and an attempt to determine which language the characters speak - Russian or Abkhaz. All this seems especially important in connection with the conclusions about the possibilities of self-preservation of the nation in the modern world, which the author cites in his literary testament, a kind of postscript to the novel “Sandro from Chegem” - the story “Sofichka”.